Assessing the impacts of sediments from dredging on corals. Issue 1 (15th January 2016) - Jones, Ross; Bessell-Browne, Pia; Fisher, Rebecca; Klonowski, Wojciech; Slivkoff, Matthew
Abstract: There is a need to develop water quality thresholds for dredging near coral reefs that can relate physical pressures to biological responses and define exposure conditions above which effects could occur. Water quality characteristics during dredging have, however, not been well described. Using information from several major dredging projects, we describe sediment particle sizes in the water column/seabed, suspended sediment concentrations at different temporal scales during natural and dredging-related turbidity events, and changes in light quantity/quality underneath plumes. These conditions differ considerably from those used in past laboratory studies of the effects of sediments on corals. The review also discusses other problems associated with using information from past studies for developing thresholds such as the existence of multiple different and inter-connected cause-effect pathways (which can confuse/confound interpretations), the use of sediment proxies, and the reliance on information from sediment traps to justify exposure regimes in sedimentation experiments. Highlights: Water quality was measured during capital dredging programmes near reefs. Measurements included sediment concentration, particle size, and light quality/quantity. Conditions in situ differ noticeably from past, lab-based studies with corals. Guidance is given for future research to be able to better assess the risk of dredging.